Assessment of Total Quality Management Practices and Organizational Development. (The case of Telecom Services Sector of Pakistan) - Sajjad, Faiza; Amjad, Shehla (Richtmann Publishing, 2011)
The main purpose of this study is to determine the various benefits an organization can derive from the application of totalquality management practices, or the relationship between total quality management and quality outcomes/benefits in services sector oftelecom industry of Pakistan. The study is based on primary and secondary data. Eight most important constructs were found throughliterature review for conceptual framework in this study. Primary data is collected through questionnaires. The same questionnaire wasused in comparison of TQM practices in different countries such as India, USA, Mexico, China and Norway. The theoreticalframework adopted is by Raghunathan et al. (1999). Findings revealed that TQM practices and implementation have positive effects onquality benefits or outcome (productivity, profitability, competitive position, reduce customer complaints, cost reduction, reduce rework level,reduces scrap level, stay in business) in services sector of telecom industry of Pakistan. Benchmarking also plays a significant role in thedevelopment of organizations. In addition to the research data, findings from different field studies and other research works have furthersupported conclusion drawn from this research, that TQM practices have positive effect on organizational development. The findings basedon this empirical research would be useful to both decision makers and researchers.